Spatial Quality Concept Through Direction of View Accommodating Work for Home Activities in Official Houses - Bodromulatsih, Ratri; Defina, Ima; Cahyadini, Sarah (ASTONJADRO, 2024)
In the last 20 years, working from home (WFH) has become more common and even more popular due to the outbreak of the infectious disease COVID-19. This condition is a challenge for residences that are not designed for living and working, especially for houses that are not designed for work, such as official residences. Apart from that, there are restrictions on changing the physical structure of the building that residents must comply with. Knowing these conditions, it is necessary to pay attention to the quality of the building so that the building remains able to accommodate these activities. As a method to achieve research objectives, this research uses two strategies, namely qualitative as the dominant method and quantitative as the supporting method. Quantitative data as a grouping of resident data and as a basis for exploring data in the next stage, namely the qualitative stage. Qualitative data was analyzed using thematic analysis, to find themes related to quality spatial conditions to accommodate work activities at home. Based on the three existing unit types, the presence of other individuals constitutes unwanted visual content. In type 4, residents who work in the bedroom do not get the desired view because the distance between the units is too close. So that quality spatial conditions can be realized, it is necessary to pay attention to the following concepts: (1) Space presents the desired visual content (2) Uses furniture that is essential for work (3) Provides a personal touch (4) Windows with features that can regulate visual privacy.